Three dimensional digital reconstruction of the jaw adductor musculature of the extinct marsupial giant Diprotodon optatum - Sharp, Alana C. (PeerJ Inc., 2014)
The morphology and arrangement of the jaw adductor muscles in vertebrates reflects masticatory style and feeding processes, diet and ecology. However, gross muscle anatomy is rarely preserved in fossils and is, therefore, heavily dependent on reconstructions. An undeformed skull of the extinct marsupial, Diprotodon optatum, recovered from Pleistocene sediments at Bacchus Marsh in Victoria, represents the most complete and best preserved specimen of the species offering a unique opportunity to investigate functional anatomy. Computed tomography (CT) scans and digital reconstructions make it possible to visualise internal cranial anatomy and predict location and morphology of soft tissues, including muscles. This study resulted in a 3D digital reconstruction of the jaw adductor musculature of Diprotodon, revealing that the arrangement of muscles is similar to that of kangaroos and that the muscle actions were predominantly vertical. 3D digital muscle reconstructions provide considerable advantages over 2D reconstructions for the visualisation of the spatial arrangement of the individual muscles and the measurement of muscle properties (length, force vectors and volume). Such digital models can further be used to estimate muscle loads and attachment sites for biomechanical analyses.